Modelling the rheological properties of bituminous binder using a mechanical model - Nur Izzi, Md. Yusoff, Dr.; Mounier, Damien; Ginoux, Marc-Stephane; Airey, Gordon D., Prof. (The Institution of Engineers, Malaysia (IEM), 2013)
Link to publisher's homepage at http://www.myiem.org.my/